RHK MODEL PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM BERBASIS MODERASI BERAGAMA DI PERGURUAN TINGGI UMUM - Riza Hadikusuma; Hafiduddin Hafiduddin; Prasetya Irwan (Politeknik Negeri Jakarta, 2025)
This article explains the curriculum development model for Islamic Religious Education courses based on religious moderation in public universities. Curriculum development like this is important so that Islamic Religious Education courses are able to make students have tolerant religious perspectives, attitudes and behavior amidst the diversity of religious life in society. This article is the result of research conducted at the State Polytechnic using a qualitative approach. The data collection methods that will be used are interviews with lecturers who teach PAI courses at various public universities as well as literature studies of scientific articles and books about Islamic Religious Education and religious moderation. Analysis of the collected data is used to formulate a model for curriculum development for PAI courses based on religious moderation. The results of the research conclude that developing a curriculum for Islamic Religious Education courses based on religious moderation is considered important and urgent in order to prevent students from extreme attitudes towards religion. The curriculum development was carried out by formulating the objectives of the Islamic Religious Education course based on religious moderation, determining student learning experiences, managing learning experiences and evaluation. The obstacle that arises is human resources, namely lecturers who teach courses who do not fully understand and realize the importance of the values ​​of religious moderation in learning Islamic Religious Education courses